1996
DOI: 10.1002/pro.5560050115
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐induced perturbation of ANS‐apomyoglobin complex: Frequency domain fluorescence studies on native and acidic compact states

Abstract: The pressure dependence of the flexibility of the 8-anilino-1-naphthalene sulfonate (ANS)-apomyoglobin complex was investigated in the range between atmospheric pressure and 2.4 kbar by frequency domain fluorometry. We examined two structural states: native and acidic compact. The conformational dynamics of the ANSapomyoglobin complex were deduced by studying the emission decay of ANS, which can form a noncovalent complex with the apoprotein in both the native and the acidic compact forms. Because the free flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
0
13
1
1
Order By: Relevance
“…At low pH and specific salt concentrations, myoglobin forms various destabilized structures (usually indicated as I and E forms) that are variably extended, depending on conditions. Thermodynamic and kinetic studies have shown that the I form contains a tight core consisting of the intersection of the AGH helices and loose solvated helical regions portions of the B-F loop [Barrick and Baldwin, 1993;Fink, 1995;Bismuto et al, 1996]. A species formed at even lower pH and low salt, the E (extended) form, contains essentially only the AGH core and is otherwise very extended [Challender et al, 1998;Baldwin and Rose, 1999a,b].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At low pH and specific salt concentrations, myoglobin forms various destabilized structures (usually indicated as I and E forms) that are variably extended, depending on conditions. Thermodynamic and kinetic studies have shown that the I form contains a tight core consisting of the intersection of the AGH helices and loose solvated helical regions portions of the B-F loop [Barrick and Baldwin, 1993;Fink, 1995;Bismuto et al, 1996]. A species formed at even lower pH and low salt, the E (extended) form, contains essentially only the AGH core and is otherwise very extended [Challender et al, 1998;Baldwin and Rose, 1999a,b].…”
Section: Discussionmentioning
confidence: 99%
“…In each substate the excited tryptophan experiences a specific microenvironment that affects its fluorescence lifetime. Myoglobin molecules fluctuate fast at acidic pH and in the presence of salt among unfolded and partly folded states with characteristics of molten globule, i.e., a native-like architecture but with labile tertiary interactions [Barrick and Baldwin, 1993;Bismuto et al, 1993Bismuto et al, , 1996Fink, 1995]. These acidic forms of myoglobin with a-helix content come out during the initial stages of myoglobin refolding, and in the folded state pack against each other with large hydrophobic contact areas forming the heme binding site.…”
mentioning
confidence: 98%
“…The fluorescence lifetime of TMR is 2.2 ns, whereas the lifetime of ANS in aqueous buffer is less than 100 ps. 17 With this sample, the TMR fluorescence is observed in a background from a large number of weakly fluorescent ANS molecules. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This pronounced sensitivity of ANS to its environment makes it an excellent probe for studies of protein stability and dynamics. 17 Figure 4a shows the fluorescence autocorrelation function for dye-labeled myoglobin (diffusion only) and for the apoMb-ANS sample (diffusion and reaction) described in the Experimental section. These data were taken with the excitation beam diameter reduced from 5 to 3 mm.…”
Section: Resultsmentioning
confidence: 99%
“…9 Frequency domain fluorometry is one of the most common spectroscopic methods to elucidate the structural and dynamic aspects of tryptophan containing proteins. [10][11][12] However, the photophysics of indolic residues in proteins is complex and involves multiple nonradiative pathways, such as solvent quenching, excited-state proton transfer, excited-state electron transfer, and intersystem crossing. [13][14][15][16] The preferential de-excitation pathways are determined by the indolic conformers mainly present in the ground state, and by the composition and mobility of the different environments experienced in the excited state.…”
Section: Introductionmentioning
confidence: 99%